Analysis of dried blood spots is a feasible alternative for detecting ephedrine in doping control. Issue 10 (1st July 2022) - Solheim, Sara Amalie; Thomas, Andreas; Ringsted, Thomas Kamm; Thevis, Mario; Breenfeldt Andersen, Andreas; Holm‐Sørensen, Henrik; Nordsborg, Nikolai B.; Mørkeberg, Jakob
Abstract: Dried blood spot (DBS) testing allows fast, easy and minimally invasive collection of microvolumes of blood. In an anti‐doping context, DBS testing has particular relevance for substances prohibited in‐competition only such as ephedrine, which is currently detected by urine analysis, because DBS can add information about the blood drug concentrations during the in‐competition period. Several collection methods and devices exist for DBS collection from different anatomical sites. Thus, agreements between concentrations of target analytes in DBS samples from different sampling sites, along with between DBS and those in conventional venous plasma samples, need to be evaluated. Herein, we collected matched upper‐arm DBS, fingerprick DBS and venous plasma samples from eight healthy male subjects in an 8‐h period following oral administrations of 20 mg ('low dose') and 60 mg ('high dose') of ephedrine. We show that the use of alternative sampling sites and matrices is a feasible possibility for ephedrine analysis in doping control. We observed very good agreement between collection sites and that specificity and sensitivity can be upheld despite use of an alternative collection site. However, potential concentration differences between DBS and venous plasma should be considered, and distinct threshold might be necessary if implementing both blood matrices in ephedrine analysis. Abstract : A wide range of collection methods and devices exist for DBS collection from different anatomical sites. We collected matched upper‐arm DBS, fingerprick DBS and venous plasma samples after oral ephedrine administrations and compared the ephedrine concentrations. The results show that the use of alternative sampling sites and matrices is a feasible possibility for ephedrine analysis in doping control.